In vitro activity of hybrid lavender essential oils against multidrug resistant strains of Pseudomonas aeruginosa - Donadu, Matthew; Usai, Donatella; Pinna, Antonio; Porcu, Tiziana; Mazzarello, Vittorio; Fiamma, Maura; Marchetti, Mauro; Cannas, Sara; Delogu, Giovanni; Zanetti, Stefania; Molicotti, Paola (The Journal of Infection in Developing Countries, 2018)
Introduction: Lavender is an evergreen shrub native to Northern Africa and other mountainous Mediterranean regions. It grows throughout Southern Europe, the United States, and Australia. Lavender essential oil has been used since ancient times and is known for its anti-inflammatory, antidepressant, antiseptic, antifungal and antimicrobial properties. Methodology: in this study, the antimicrobial activity of two Lavender essential oils (Lavanda sumian and Lavanda grosso) against 16 multidrug-resistant P. aeruginosa strains from clinical ocular samples taken from migrant patients has been investigated. The in vitro cytotoxic activity on human Wong-Kilbourne derivative (WKD) conjunctiva cells from healthy patients and nitric oxide synthase (NOS) activity on murine macrophage (J774.1A) were also evaluated. Results: L. sumian showed lower antimicrobial activity when compared to L. grosso. Both lavender oils tested had no cytotoxic effect at very low concentrations, mostly L. grosso. The essential oils extracted from L. sumian and L. grosso significantly reduced NOS in a cell model. Conclusion: Increase in drug resistance and lack of new antibiotics may encourage the development of natural antimicrobial treatments.